2018
DOI: 10.13075/ijomeh.1896.01298
|View full text |Cite
|
Sign up to set email alerts
|

The system of values and styles of success in the medical career: A longitudinal study

Abstract: Objectives: The purpose of the study was to investigate the relation between system values during medical education and styles of success in the medical career. Material and Methods: The participants were first examined when they applied to the medical school. Questionnaires were given to these students each academic year. Medical doctors who had participated in the first phase of the study completed a questionnaire 4 years after their graduation, too. The baseline questionnaire measured the system values. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In an series of publications on the type of careers the authors identified three types of medical careers: "Committed-satisfied with career", which are physicians committed to their work the most with the highest level of work stress; "Clever-satisfied with life", the least committed to their work, but deriving the most benefit from it; and "Bright-competent", which are the most competent, but with problems managing their lives. The "Committed" type proved to be at the highest risk of BS, whereas "Clever" at the lowest [46][47][48][49][50]. Other papers in our review have also identified individual character or personality traits as potentially significant factors.…”
Section: Personality Coping Strategies and Personal Resources And Bsmentioning
confidence: 71%
See 2 more Smart Citations
“…In an series of publications on the type of careers the authors identified three types of medical careers: "Committed-satisfied with career", which are physicians committed to their work the most with the highest level of work stress; "Clever-satisfied with life", the least committed to their work, but deriving the most benefit from it; and "Bright-competent", which are the most competent, but with problems managing their lives. The "Committed" type proved to be at the highest risk of BS, whereas "Clever" at the lowest [46][47][48][49][50]. Other papers in our review have also identified individual character or personality traits as potentially significant factors.…”
Section: Personality Coping Strategies and Personal Resources And Bsmentioning
confidence: 71%
“…Series: [46][47][48][49][50] 2011: low level of the sense of comprehensibility in the 6th, high level of "trait" anxiety in the 4th, high level of depression in the 3rd, low need for social approval in the 3rd year of medical school 2012: -type of career "Committed-satisfied with career"-the most committed to their work with the highest level of work stress 2012: -type of career "Clever-satisfied with life"-the least committed to their work, but deriving the most benefit from it -well-being and life satisfaction 2014: -high sense of coherence at medical studies 2016: -taking actions and dealing directly with the problem at medical studies 2018: -family, freedom, happiness, mature love, self-respect, social recognition and wisdom [8] -negative assessment of healthcare, -poor relationships between healthcare professionals -positive assessment of conditions offered to in-patients -positive patients' attitude toward physicians -negative patients' attitude toward nurses -seniority -positive general assessment of healthcare, -negative assessment of patients' attitude toward physicians -proper relationship between healthcare professionals [55] -high level of perceived stress -large number of duties per month -seniority -frequent use of annual leave…”
Section: Study Factors Contributing To the More Frequent Or Increasedmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors can identify during medical education which students will be at risk of professional burnout after studies. The most important differences between students who can have burnout later as doctors and those at lower risk are family security, freedom, happiness, mature love, self-respect, social recognition, and wisdom 29 .…”
Section: Discussionmentioning
confidence: 99%